Critical Review of Character Education in Vocational High Schools in Era Society 5.0 - Nizlel Huda; Nurhanurawati Nurhanurawati; Ajeng Gelora Mastuti; Mazlini Adnan (Review of Education, Science, and Technology, 2025)
The rapid advancement of digital technology and the accelerated pace of social transformation have fundamentally reshaped work, learning, and human interaction, making character education increasingly strategic in Vocational High Schools (SMKs). This study presents a critical review of national and international literature to evaluate the relevance of character education in the Society 5.0 era, identify implementation challenges, and propose strategic directions for adaptive and contextually grounded practice. The analysis indicates that effective character education requires a multidimensional approach, integrating moral, social, spiritual, and professional competencies through holistic curricula, extracurricular programs, school leadership, and stakeholder collaboration. Technology offers opportunities to enhance engagement, digital literacy, and collaboration, yet it also introduces risks such as distractions, ethical dilemmas, and gaps in digital competence. Key challenges include misalignment between school programs and industry demands, inconsistent integration of religious and digital values, and varied stakeholder involvement. Therefore, character education must operate as an ecosystemic effort, balancing technological innovation with ethical and humanistic values to produce SMK graduates who are competent, ethical, and resilient in meeting the demands of Society 5.0